Correction of maxillary hypoplasia using modifi cation of Anterior maxillary distraction device in a patient with Binder's Syndrome- Case report - Mathew PC; Rohini Kanitkar; Arun Ramaiah; Hermann Sailer (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
This is the case report of a 20year old female, affected by Binders Syndrome reported to our hospital and was operated for maxillary hypoplasia using modifi cations of the standard Anterior Maxillary Distraction (AMD) device. This helped in rehabilitation of the patients anterior and lateral profi les; thereby giving a satisfactory cosmetic appearance to the patient.